Chronic tophaceous gout presenting with severe hypercalcemia - A rare clinical entity - Jagmeet Singh; Rohit Raina; Ishan Garg; Vikas Garg (Current Medicine Research and Practice)
Gout is an inflammatory arthritis caused by the accumulation of monosodium urate crystals within the synovial fluid and surrounding tissues. This condition is closely linked to hyperuricaemia, a serum urate concentration of 6.8 mg/dL or higher. If hyperuricaemia is not properly managed, the disease may progress to chronic tophaceous gout, which involves long-term joint damage and deposition of crystal aggregates (tophi) in joints and soft tissues. In this case report, we describe the case of a 62-year-old male who presented with altered mental status, generalised weakness, poor oral intake and diffuse body pain. Laboratory tests revealed severe hypercalcaemia, which is a rare presentation. The patient was treated with intravenous saline hydration, calcitonin and prednisone, which improved kidney function and normalised calcium levels.